Astrovirus associated gastroenteritis in a children's ward. Issue 10 (October 1977) - Kurtz, J B; Lee, T W; Pickering, D
Abstract : During an outbreak of gastroenteritis in a paediatric ward astroviruses were found in faeces from 17 to 27 symptomatic children and from four of 14 members of the staff with diarrhoea. No viruses were found in 10 asymptomatic children. Fourteen of the 21 astrovirus excretors were free of any recognised pathogens, but in the other seven, rotaviruses or pathogenic bacteria were also present. Serological evidence of astrovirus infection was obtained in five adults and two children.